Effect of Seed Priming Treatments on Seed Yield and Seed Quality Parameters in Chickpea (Cicer arietinum L.) cv BDNGK-798 - ZADE VR; MISAL AM; WANKHADE MP; RATHOD AH; INGOLE RR (Seed Research, 2024)
A field experiment was conducted at experimental farm of AICRP on safflower, Vasantrao Naik Marathwada Krishi Vidyapeeth, Parbhani during Rabi 2022-23 using chickpea cv BDNGK-798 to evaluate the effect of different seed priming treatments on growth, seed yield and yield attributing characters in chickpea. Experiment was laid out with seven treatments including one control, replicated thrice in Randomized Block Design. The chickpea cv. Virat (BDNGK-798) seed was primed with different growth regulators viz., Gibberellic acid @ 100ppm, Indole Acetic Acid @ 200 ppm, Salicylic Acid @ 100 ppm, KN03 @ 100 ppm, PEG @ 7%, CaCl2 @2% along with control. The observations were recorded on following characters viz., days to 50 per cent flowering, days to physiological maturity, plant height (30 DAS) (cm), plant height (60 DAS) (cm), primary branches / plant (30 DAS), primary branches / plant (60 DAS), secondary branches / plant (60 DAS), number of pods/ plant, pod weight /plant (g), seed yield /plant (g), biological yield /plant (g), seed yield /plot (kg), germination percentage, seed vigour -I and seed vigour -II. All the priming treatments were found effective over control. However, the treatment with calcium chloride (CaCl2) @ 2% was found more effective among all treatments.